SISTEM INFORMASI PENGOLAHAN DATAAKADEMIK SISWA BERBASIS WEB PADA SMA BUDI AGUNG - Albert Albert; Wasino Wasino; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
The information system application program used by Budi Agung High School to process student academic data to store all school academic data so the data will be stored neatly in the database so it will be easy to access easily, quickly, precisely, and accurately. This website also has a decision support system that can helping schools in prospective scholarship program with the Simple Additive Weighting selection method. This website is well designed using PHP programming language and uses MySQL and phpMyAdmin as database. The testing using whitebox method. The method used in developing software is the Rapid Application Development method. The results obtained are SMA Budi Agung uses a website-based application program to obtain information about student data, teacher data, class data, announcement data, grade data, attendance data, and schedule data in the form of reports. Admin also has full access rights to add, update, and delete existing data in the database.